The Rise of Wooden Houses in the United States: Structural Evolution, Prefabrication, and Suburbanisation - Şişman, Muhammet Emin (İstanbul Üniversitesi, 2025)
This study examines the rise of wooden houses in the United States from the early colonial settlements (17th century) to the post-World War II suburban expansion (1950s). It integrates three core domains to explain this long-term transformation: (i) the structural evolution of timber construction, tracing the transition from heavy timber frames to light-frame balloon and platform systems; (ii) the industrialisation of housing through prefabrication and the mail-order system, which distributed precut houses nationwide via catalogues and rail networks; and (iii) the socio-cultural dynamics of suburbanisation that reshaped domestic architecture. The research employs a qualitative synthesis of heterogeneous historical materials, including archival documents (such as government bulletins and standards), company catalogues (Aladdin, Sears, E. F. Hodgson), technical reports, historical and sociological studies, period photographs, and statistical summaries. The analysis is based on historical comparison, document review, and visual analysis. The paper’s central contribution is to demonstrate—beyond single-factor explanations—how the sustained interaction between structural efficiency, standardised mass production, and cultural aspiration jointly produced a resilient and dominant wooden-house tradition. By periodizing turning points and tracing mechanisms such as cost reduction and accessibility, the study offers a coherent framework providing insights for contemporary housing policies in nations seeking sustainable and culturally resonant timber-based housing solutions.
Keywords: Architectural Design; Mimari Tasarım